REVISITING RACIAL POTRAYAL IN THE AMERICAN POPULAR FILM - Primadewi, Nerfita (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2021)
This article examines the ways in which race has played out in American popular film, from early silent films to recent films.  Even though film, especially cartoon, often perceived as merely entertainment, it is not free from racial biases. Ranging from D.W. Griffith’s Birth of a Nation to James Cameron’s True Lies to Ron Clement’s Aladdin to Scott Derrickson’s Doctor Strange, Hollywood cinema has been feeding not only American audiences but also non-American audiences bias stereotypical portrayal of people of color and their culture. This study will discuss how is race constructed, countered, and accommodated in such films, and problematized these types of films in relation to racial tension in the US nowadays.